DO WE NEED TO GIVE MEASLES VACCINE TO CHILDREN EARLIER THAN THE CURRENTLY RECOMMENDED AGE? - Jamal, Ammarah; Yahya, Yousuf; Karim, Muhammad Tariq (Journal of Ayub Medical College Abbottabad, 2018)
Background: Measles is a leading cause of death among children. No specific drug has yet been discovered to treat measles but an available vaccine can effectively prevent the infection. In Pakistan children are vaccinated against measles by two doses given at age of nine months onward. The last few years have witnessed an increasing number of measles cases at age lower than nine months. Methods: Secondary data analysis of the records of Expanded Program on Immunization from all districts of Sindh was performed from January-April 2016. Data included all patients of any age or gender, fulfilling the World Health Organization case definition of measles, along with positive IgM antibodies for measles in their blood. Data was analysed using windows SPSS version 21.0. Results: Analysis of 658 confirmed measles cases showed an age range of 3 months to 336 months with a mean of 32.82. Most patients (41.4%) belonged to age group 10-24months. Some noteworthy18% of cases were ‰¤9 months old including 1.8% patients who were ‰¤6 months age. An unexpected 76 (11.6%) were >60 months of age. 50.6% of the cases were male while 49.4% were female. Most of the patients (73.9%) belonged to urban areas. Conclusion: We conclude that a sizeable number of children are infected by measles before reaching the age of first recommended inoculation against measles. It is affecting people at both extremes of life ranging from as young as three months up to 28 years of age. Keywords: Measles; vaccination; child; immunity; infant; infection